The role of islamic institutions in the adoption of reduce, reuse, and recycle (3r) practices among Muslim communities in Malaysia. - Idris, N. (2012)
It has been argued in the literature that religious belief has a role to play in dealing with environmental issues and enhancing environmental practices. In line with this perspective, it is interesting to observe that Muslim communities have started to use the Islamic institutions as an organizational and institutional platform for shown their environmental programmes. In some mosques and small mosques (surau), inspiring green programmes such as the 3R programme have also conducted. However, previous research on the role of religious community in enhancing environmental practices is mostly discussed at the theoretical level and only a handful have undertaken in systematic empirical research on this topic. The purpose of this study is to explore an innovation process in Islamic institutions which refer to ‘mosque and small mosque’ (surau), as a central organisational and institutional structure in the Muslim community especially in carry out the 3R programme. In addition, this study will also identify the potential role of mosque and surau in adoption of 3R program. The framework for this research is based on the adaptation of theoretical frameworks: “The adoption of innovation of organisational process framework” developed by Everett Rogers (2005). The article is mainly based on a qualitative study. It employs an in-depth case study on the 3R activities conducted in mosque at Rembau, Negeri Sembilan, Malaysia that are involved in the “Amal Jariah melalui Kitar Semula di Masjid” programme and 3R programme from small mosque - Surau al-Husna in Shah Alam, Selangor. In this research, semi-structured interview and focus group study have been carried out. Preliminary work reveals the inspired results. From our key findings, both Islamic institution; mosque and surau have a big advantages in playing its role due to its systematic organisational structure and unique ability to adopt the 3R programme efficiently. The potential role can be seen in stability in organisational structure, formal and non-formal environmental education, strong element of leadership, provide a recycling point facilities, and Islamic institution as a community center and also ‘innovation laboratory’. Another role that should be underlined is the way Islamic institution in cultivating the concept of charity/giving alms (sedekah) through recycling - where people have the opportunity to contribute their recyclable items to generate money for mosque and surau. These case studies is hopefully can gives inspiration and motivation to other religious institution in acting the good deeds towards environment through 3R practices.